The roles of experiences and risk perception in the practice of preventative behaviors of COVID-19. (2nd January 2022) - Fadel, Tina; Travis, Justin; Harris, Scott; Webb, Ginny
ABSTRACT: Understanding the variables contributing to the practice of COVID-19 preventative behaviors is important in order to provide the best education to the community. Here, we aim to determine what factors affect an individual's compliance to suggested COVID-19 preventable behaviors. We also aim to determine what contributes to an individual's willingness to get the COVID-19 vaccine. This study surveyed residents of South Carolina, USA to analyze factors relating to preventative behavior. Survey respondents were asked a series of questions using Qualtrics survey platform. The questions included demographics, experiences with COVID-19, knowledge about the disease, and the practice of preventive behaviors. Results of this study demonstrate that demographic differences (e.g. being older, female, and more educated) and psychological differences (e.g. more COVID-19 personal experiences, perceived susceptibility and severity) are all shown to be significantly correlated with COVID-19 preventative behaviors and vaccine willingness. The factors that influence an individual's preventative behaviors and vaccine willingness are important to understand so that public health officials can best tailor and target their educational efforts.